Influence on alveolar resorption of the buccal bony plate width in the edentulous ridge expansion (ERE) - an experimental study in the dog - Beolchini, Marco; Lang, Niklaus P.; Ricci, Emanuele; Bengazi, Franco; Garcia Triana, Barbara; Botticelli, Daniele [UNESP] (Wiley-Blackwell, 2015)
Objective: To compare the hard tissue changes at implants installed applying edentulous ridge expansion (E.R.E.) at sites with a buccal bony wall thickness of 1 or 2 mm.Material and methods: In six Labrador dogs, the first and second maxillary incisors were extracted, and the buccal alveolar bony plates and septa were removed. After 3 months of healing, partial-thickness flaps were dissected, and the E.R.E. was applied bilaterally. Hence, an expansion of the buccal bony crest was obtained in both sides of the maxilla with a displacement of either a 1- or a 2-mm-wide buccal bony plate at the test and control sites, respectively. After 3 months of healing, biopsies were obtained for histological analyses.Results: A buccal vertical resorption of the alveolar crest of 2.3 +/- 0.8 and 2.1 +/- 1.1 mm, and a coronal level of osseointegration at the buccal aspect of 2.7 +/- 0.5 and 2.9 +/- 0.9 mm were found at the test (1 mm) and control (2 mm) sites, respectively. The differences did not reach statistical significance. The mean values of the mineralized bone-to-implant contact (MBIC%) ranged from 62% to 73% at the buccal and lingual sites. No statistically significant differences were found. Horizontal volume gains of 1.8 and 1.1 mm were observed at the test and control sites, respectively, and the difference being statistically significant.Conclusions: Implants installed using the E.R.E. technique yielded a high degree of osseointegration. It is suggested that the displacement of buccal bony plates of 1 mm thickness is preferable compared with that of wider dimensions.
Keywords: animal study; bone augmentation; bone healing; bone width; buccal bony plate; dental implants; edentulous ridge expansion; histology; implant dentistry; ridge expansion; split crest